A Sensitive "Optical Nose" for Detection of Volatile Organic Molecules Based on Au@MOFs Nanoparticle Arrays through Surface‐Enhanced Raman Scattering. (3rd March 2020) - Men, Dandan; Feng, Sujuan; Liu, Guangqiang; Hang, Lifeng; Zhang, Tao
Abstract: Surface‐enhanced Raman scattering (SERS) is an effective technique for detecting toxic gas and volatile organic molecules (VOMs); however, recent SERS‐based gas sensors have disadvantages and lack an effective approach to capture toxic gas and insufficient reproducibility of SERS substrates. Herein, a facile strategy is developed to integrate metal‐organic frameworks with Au nanoparticle (NP) arrays to form Au@ZIF‐8 NP arrays, which can be used as an "optical nose" based on SERS to detect toxic VOMs with good reproducibility and sensitivity. Toluene as a target molecule is recognized at ppm levels by the Au@ZIF‐8 NP arrays in situ. And the analytical enhancement factor of Au@ZIF‐8 NP arrays for toluene is about 1.2 × 10 5 . Importantly, this SERS substrate can also detect the 1‐butanol molecule, which provides an idea for designing a universal VOM sensor. In addition, the coating method of the ZIF‐8 shell can be extended to synthetize various NPs@ZIF‐8 core–shell composites, such as Au nanospheres@ZIF‐8, Au@Ag nanorods@ZIF‐8, PS microspheres@ZIF‐8, and Fe2 O3 microellipsoids@ZIF‐8 composites. Abstract : 2D Au@ZIF‐8 nanoparticle (NP) arrays as surface‐enhanced Raman scattering (SERS) substrates are prepared by integrating metal‐organic frameworks with Au NP arrays. For this SERS substrate, toluene vapor is recognized at ppm levels. It also displays good reproducibility due to a highly ordered structure. In addition, the coating method of the ZIF‐8 shell is a general method to synthetize various NPs@ZIF‐8 core–shell composites.